Pengabdian Pelatihan Stimulasi Bicara Anak dengan Program “KartoNg Mejik” : Indonesia - Budi Susilo, Markus Nanang Irawan; Widyawati, Sri; Asih, Gusti Yuli (UII, 2024)
Speaking is a form of communication that appears in the stages of human development and needs to be trained from an early age. Not infrequently in this process children experience problems, namely speech delays even though children have been trained a lot and live in a supportive environment. The problem of speech delay makes parents tend to be anxious, confused, and panicked, especially if they do not have adequate information or knowledge related to the problem of speech delay and how to prevent and overcome it. One place that can help parents in overcoming the problem of speech delays is the nearest PAUD-KB, where parents hope that teachers can help overcome children's speech delay problems. However, teachers also often experience limited information and knowledge about how to deal with speech delays as well so that their efforts and assistance are not optimal. The Community Service Team of the Faculty of Psychology is here to help provide psychoeducation related to the introduction, prevention, and handling of children's speech delays through training and assignments on children's speech stimulation with the